Tibetan students at an interior university in China: negotiating identity, language, and power. Issue 2 (2nd April 2020) - Wang, Hao; Chao, Xia; Sun, Shunv
ABSTRACT: Using Norton's conception of identity and Harré and Moghaddam's positioning theory, the current study examines how a group of Tibetan students' situated context affects their identity (re)construction in a traditionally non-multiethnic interior university in China. Drawing from interview, biographies, document, and artefact data, our findings suggest that the construction and negotiation of ethnic Tibetan students' identities is a complex, power driven, and unstable process. In particular, the participants' identity positioning at the host university is inextricably linked to stereotypical images of Tibetans, linguistic integration in the interior academic environment via English, Putonghua, and Tibetan language, and larger institutional practices. Tangible pedagogical implications are discussed, such as providing critical multicultural and multilingual education at the university are discussed.